2007
DOI: 10.1111/j.1440-1827.2007.02118.x
|View full text |Cite
|
Sign up to set email alerts
|

Solid–papillary carcinoma of the breast: Clinicopathological study of 20 cases

Abstract: The purpose of the present paper was to evaluate the clinicopathological and biological features of 20 Japanese patients with solid-papillary carcinoma of the breast (SPC) or SPC associated with invasive breast cancer. All the patients were Japanese women, including two sisters. The mean age was 66.0 years. The incidence of SPC among all the breast cancers treated at two institutions was 1.1% and 1.7%, respectively. The mean disease-free interval was 4 years 11 months. Axillary lymph node metastasis or tumor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
87
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 25 publications
9
87
1
Order By: Relevance
“…1,2,7 CLINICAL FEATURES Solid papillary carcinoma is an uncommon lesion that affects primarily elderly women, with a mean age of 72 years in one series. 1,2,4 However, occasionally this tumor can affect patients younger than 50 years.…”
Section: Histogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,7 CLINICAL FEATURES Solid papillary carcinoma is an uncommon lesion that affects primarily elderly women, with a mean age of 72 years in one series. 1,2,4 However, occasionally this tumor can affect patients younger than 50 years.…”
Section: Histogenesismentioning
confidence: 99%
“…1,2,4 However, occasionally this tumor can affect patients younger than 50 years. 6,7 Rarely, SPC can occur in male patients. 6 Nearly 95% of cases are unilateral, and the majority of tumors arise in the central area of the breast.…”
Section: Histogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5, I through L, shows an example of SPC with negative CK5 and p63 staining. A study 21 reported that, of 20 SPC cases, at least 10 (50%) expressed one or more neuroendocrine markers. Solid papillary carcinoma should be differentiated from UDH, which is positive for CK5 and CK5/6.…”
Section: Distinguishing Between Papillary Lesionsmentioning
confidence: 99%
“…SPC is a tumor composed of circumscribed nodules of epithelial cells that are typically ovoid or spindle-shaped with low nuclear grade, and it develops predominantly in elderly patients (3). There are few case reports on SPCs and most studies report on pathologic findings in SPC patients (4,5). SPCs are mostly located in the central part of the breast, and 95% of SPCs are present in unilateral breasts (6).…”
Section: Introductionmentioning
confidence: 99%